Assistive Handlebar Based on Load Cells as Attendant Steering Device - Trujillo-León, Andrés; Sánchez-Sánchez, Cristina; Castellanos-Ramos, Julián; Vidal-Verdú, Fernando (IEEE, 2018)
The increase in the life expectancy has pushed the interest in developing assistive technologies to extend the autonomy of the elderly. Mobility is a major concern for this population, and aids should be designed to be friendly and intuitive. This paper proposes a device that replaces the attendant joystick of a wheelchair by an assistive steering device based on load cells. The resulting device is tested by twelve volunteers in a tracking task that consists in following a path. The deviation from the target trajectory is registered and the results are presented and analyzed.
Keywords: Tecnología de la rehabilitación; Wheelchairs; Trajectory; Lasers; Task analysis; Force; Force sensors